Mechanisms of carbon nanotube-induced toxicity: Focus on oxidative stress - Shvedova, Anna A. (Toxicol Appl Pharmacol, 2012)
Nanotechnologies are emerging as highly promising technologies in many sectors in the society. However, the increasing use of engineered nanomaterials also raises concerns about inadvertent exposure to these materials and the potential for adverse effects on human health and the environment. Despite several years of intensive investigations, a common paradigm for the understanding of nanoparticle-induced toxicity remains to be firmly established. Here, the so-called oxidative stress paradigm is scrutinized. Does oxidative stress represent a secondary event resulting inevitably from disruption of biochemical processes and the demise of the cell, or a specific, non-random event that plays a role in the induction of cellular damage e.g. apoptosis? The answer to this question will have important ramifications for the development of strategies for mitigation of adverse effects of nanoparticles. Recent examples of global lipidomics studies of nanoparticle-induced tissue damage are discussed along with proteomics and transcriptomics approaches to achieve a comprehensive understanding of the complex and interrelated molecular changes in cells and tissues exposed to nanoparticles. We also discuss instances of non-oxidative stress-mediated cellular damage resulting from direct physical interference of nanomaterials with cellular structures.